Effects of dietary glutathione supplementation on the growth performance, nutrient digestibility, antioxidant function and intestinal morphology in growing male minks - Beibei Zhang; Yang Ci; Keru Li; Yanhong Xu; Menghao Li; Wenli Li (PLoS ONE, 2026)
This study investigated the effects of dietary glutathione (GSH) supplementation on growth performance, nutrient digestibility, amino acid digestibility, antioxidant capacity, and intestinal morphology in growing male minks. Sixty two-month-old male minks were divided into 6 groups and fed diets supplemented with 0 (control), 50, 100, 150, 200 and 250 mg/kg GSH over a 9-week trial. The results showed numerically higher growth performance and pelt quality in the groups receiving 50–200 mg/kg GSH, but these differences were not statistically significant ( P > 0.05). Dietary supplementation with 150–250 mg/kg GSH significantly increased crude fat digestibility, while 100–200 mg/kg GSH enhanced cysteine digestibility and 150 mg/kg GSH elevated the digestibility of isoleucine, leucine, tyrosine, and phenylalanine during the first four weeks ( P < 0.05). At the end of the experiment, total serum superoxide dismutase (T-SOD) activity was significantly increased with 150–250 mg/kg GSH ( P < 0.05). Serum glutathione peroxidase activity was significantly elevated by 150–200 mg/kg GSH ( P < 0.05). Hepatic T-SOD activity was significantly increased by 100 and 200 mg/kg GSH ( P < 0.05), and glutathione transferase activity was upregulated by 50, 100, and 200 mg/kg GSH ( P < 0.05). Additionally, 250 mg/kg GSH significantly raised hepatic GSH level ( P < 0.05), and both 100 and 250 mg/kg GSH significantly elevated the hepatic GSH/GSSG ratio ( P < 0.05). Furthermore, 200 mg/kg GSH significantly increased the villus height in the duodenum and jejunum ( P < 0.05). In conclusion, dietary GSH supplementation increased nutrient digestibility, antioxidant capacity and intestinal health in growing minks, with 200 mg/kg showing greater benefits, thereby providing valuable guidance for its practical use in mink nutrition.